What’s in a name? The Ligurians, a case study in ethnicity in late prehistory - Vecchi, Elisa (2023)
This dissertation discusses the archaeological evidence for the Ligurians, who are believed to have inhabited north-western Italy in late prehistory. The approach to this subject has remained substantially unchanged from the analysis of the first prehistorians: mainstream interpretations lack theoretical reflection and are deeply influenced by the written sources. Hence the need to reassess the question from a different perspective which considers the debate on the symbolic meaning of the material culture and how to interpret it. This research aims to investigate the identity of the people in late prehistoric north-western Italy, understand the meaning of ethnic labels in the written sources and verify if/how we can infer past ethnicities from the archaeological record. This is done by analysing evidence from 375 sites to define the archaeological culture of ancient Liguria between the final Bronze Age and the end of the Iron Age. The archaeological culture is then used as a basis from which to determine what artefacts, actions, social practices carry identity valencies that can be interpreted in ethnic terms. I recognise an ethnic valency to activities that can be linked to the idea of a common descent and to the emergence of a gender distinction in the grave assemblages, and argue that a group identity, which was constructed and reinforced through ritual drinking at funerals, emerged in the late 7th – 6th century BC. I conclude that the people that inhabited north-western Italy south of the Po began to express their ethnic identity in relation to the increasing competition and social changes that derived from the contacts with Etruscan communities. I claim that the term ‘Ligurian’ was not originally used to indicate a specific people and that labels used by ancient authors might not have had an ethnic meaning and/or have changed meaning across centuries. Finally, I argue that through the analysis of the archaeological evidence in its context we can detect the expression of ethnicity, but not the actual process of ethnogenesis.